The Mysticism of Arabic Calligraphy: A Love Affair between the Reed Pen and Sufism - Rasha Zenhom (Journal of Architecture, Art & Humanistic Science, 2021)
The relationship between calligraphy and mysticism has a unique inner dynamic in Islam. Arabic calligraphy has been cultivated for centuries in the context of pious everyday practice of the Sufis and Dervishes. From the symbolic interpretation of the letters to the breathing technique – calligraphy and sufic mysticism share many similarities. Many Muslim calligraphers were drawn to the spiritual teachings of the Sufis and were often followers of the Sufi Order themselves. The Sufis, on the other hand, found in calligraphy the appropriate artistic expression to visualize their contemplation of the Koranic word and thus to exercise their spirituality.Due to globalization and open skies we find ourselves standing in front of a major challenge against voices that are claiming that Islamic arts and civilization fell through and they are underdeveloped. Without trying to know the true concept of that art and without studying it's influence on the western art and intellect. So we have to confirm the philosophy of the Islamic art through artistic pieces and their influence on pioneers and how they utilize them in such a clear way at the renaissance age through works of orientalists, modern art schools and some artists who were affected by it such as (Matisse, Picasso, Kandinsky, Bulkeley, Mondrian, Vasarely) who are considered the most iconic western artists in the modern age. Then the identity of artists might be assured in the age of globalization and the 21t century which might have an impact on the western conception of Islam and Islamic arts. We find out that the research problem is at many elements: The lack of confirmation of the Islamic identity for western artists at the modern age, such as (Matisse, Picasso, Kandinsky, Bulkeley, Mondrian, Vasarely). Assuring the special elements and characteristics of Islamic arts and their influence on renaissance and orientalism. The research aim: Realizing the concept of Islamic arts and their impact on the west during the age of globalization and the 21st century. In order to achieve that we have to know: What is Islamic art? the special characteristics of Islamic arts. The influence of Islamic arts on renaissance, modern schools and orientalism.The elements of Islamic, Arabic art in (Matisse, Picasso, Kandinsky, Bulkeley, Mondrian, Vasarely) artistic pieces.